COMMUNICATION STRATEGY IN STUDENTS ’ ROLEPLAY AS FOUND IN BUSINESS ENGLISH MARKETING COMMUNICATION ( A CASE STUDY IN ENGLISH DEPARTMENT FHB UNISBANK SEMARANG) - Endang Yuliani Rahayu; Katharina Rustipa; Yulistiyanti, Yulistiyanti; Teguh Kasprabowo (LPSDI Bina Patria, 2025)
Speaking in English for students of English department is challenging activity. They like this subject as they can convey their idea in the target language to the listeners. During their process of communication in role play in the Business English Marketing Communication classroom they may find difficulties due to their lack of knowledge in the target language. Referring to Dornyei who defines communication strategy as a systematic technique used by the speakers to express their meaning when they face some difficulties. By applying descriptive qualitative method, the reseachers refered to Dornyei’s theory of Communication Startegy to analyze the 215 data. The most frequently communication strategy used were approximation, avoidance and Hesitation /gambit. Meanwhile negosiation, code switching, literal translation, hesitation/gambits and time gaining /filler have been used for 3 times by the students. The purpose of applying communication strategy were mostly for overcoming their difficulties, to express certain intention, to master language competence and maintain the communication with his partner